PENGARUH KUALITAS LAYANAN TERHADAP MINAT KUNJUNGAN ULANG YANG DIMEDIASI OLEH KEPUASAN PASIEN DI KLINIK RUMAH ZAKAT YOGYAKARTA - Triana Helmawati; Siti Dyah Handayani (Universitas Muhammadiyah Yogyakarta, 2014)
Rumah Zakat Clinic of Yogyakarta is a form of zakat funds in the health service and empowerment programs conducted by Indonesian Rumah Zakat Foundation. The rate of the clinic re-visit for the last 3 years data indicates the minimal amount of the re-visit patient, so that the study of service quality, patient satisfaction, and how much interest the patient to revisit is very important for future improvement. This research is a quantitative research which design with no treatment (observational) cross sectional analytic approach. The population study was all the outpatients that were in general patient status. The number of samples are 118 people. The analysis test use gradual regression test and mediation test with Sobel test. The dimensions of service quality that influence the patient satisfaction are the responsiveness and empathy, while the dimensions of tangible, reliability, and assurance have no effect to the patient satisfaction. Patient satisfaction directly affects the re-visit interest. Patient satisfaction becomes the partial mediator between the service quality dimensions namely tangible, reliability, responsiveness, assurance, empathy to the re-visit intention. There is an effect on service quality to the re-visit intention mediated by the patient satisfaction at clinic Rumah Zakat Yogyakarta.